2018
DOI: 10.1002/term.2731
|View full text |Cite
|
Sign up to set email alerts
|

Cell-enrichment with olfactory ensheathing cells has limited local extra beneficial effects on nerve regeneration supported by the nerve guide Perimaix

Abstract: The reconstruction of peripheral nerve injuries is clinically challenging, and today, the autologous nerve transplantation is still considered as the only gold standard remedy for nerve lesions where a direct nerve coaptation is not possible. Nevertheless, the functional merits of many biomaterials have been tested as potential substitutes for the autologous nerve transplant. One of the strategies that have been pursued is the combination of bioengineered nerve guides with cellular enrichment. In this present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, the results are less successful than autologous nerve grafting, the gold standard of nerve repair, which implies that cell therapy can assist nerve regeneration but it cannot replace nerve grafting altogether. It is noteworthy that a few studies have also reported that cell therapy is beneficial only for boosting nerve regeneration at the very beginning of the repair process and it does not necessarily make any difference afterward [50]. Hence, the possibility of stem cells inducing a transient positive effect on nerve regeneration should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are less successful than autologous nerve grafting, the gold standard of nerve repair, which implies that cell therapy can assist nerve regeneration but it cannot replace nerve grafting altogether. It is noteworthy that a few studies have also reported that cell therapy is beneficial only for boosting nerve regeneration at the very beginning of the repair process and it does not necessarily make any difference afterward [50]. Hence, the possibility of stem cells inducing a transient positive effect on nerve regeneration should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…[ 133 ]. Olfactory ensheathing cells (OECs) have the function of promoting nerve regeneration, but their application is limited because of the oxygen-deficient environment at the injury site [ 134 ]. Zhang et al showed that exosomal treatment significantly promoted the survival and migration of OECs in hypoxic conditions, and effectively increased brain-derived neurotrophic factor gene expression, protein levels and secretion [ 135 ].…”
Section: Role and Application Of Exosomes In Specific Cns Diseasesmentioning
confidence: 99%
“…They also exhibit great potentials for nerve repair in peripheral nerve injury-induced neuropathy ( Radtke et al, 2009b , 2011 ; Radtke and Kocsis, 2012 , 2014 ). Olfactory bulb ensheathing cells from mouse ( Goulart et al, 2016 ) and rat mediate improvements in axonal regeneration, myelination and sciatic nerve functional recovery in mouse sciatic nerve transection with a 3 mm gap, and in rat sciatic nerve transection with a 15 or 12 mm gap ( Verdú et al, 1999 ; You et al, 2011 ; Zhang et al, 2019 ), and 20 mm gap ( Guérout et al, 2011 ; Boecker et al, 2018 ), and with microsurgical nerve repair ( Radtke et al, 2009a ) and in rat sciatic nerve crush lesion ( Dombrowski et al, 2006 ), as well as in rat facial nerve transection with a 5 mm gap ( Guntinas-Lichius et al, 2001 ). As well, transplantation of olfactory mucosa significantly increases the accuracy of target reinnervation and accelerates the vibrissae movements ( Guntinas-Lichius et al, 2002 ).…”
Section: Peripheral Nerve Injury-induced Neuropathymentioning
confidence: 99%